Study on a New Type of Lelord Triangle Pump - Chen Wenjie; Zou Min; Zhu Hailin; Wang Zhiyang (Jixie chuandong)
For the defects of traditional gear pump can not pump oil in a linear way and its tooth profile line is complex,a new type of lelord triangle pump is put forward. In which the section of helical rotor is lelord triangle,and three such rotors are mount parallel. The pump can pump oil in a linear way with its rotor rotating in the same direction. Besides,the pump combined with the characteristics of gear pump and propeller. The mathematical model of lelord triangle is established. The analysis of the motion position of the lelord rotor is carried out,and the displacement and instantaneous flow rate of the internal cavity of the three rotors are calculated. It laid a foundation for the research and experiment of this pump in the later stage and a new way of thinking for pump oil in a linear way is provided.